GENETIC DETERMINANTS OF PROSTATE CANCER: A REVIEW - Kral, Milan; Rosinska, Vlasta; Student, Vladimir; Grepl, Michal; Hrabec, Martin; Bouchal, Jan (Biomedical papers, 2011)
Background: In prostate cancer, early detection and appropriate treatment remain key approaches. But given the constantly increasing incidence, prostate cancer ethiopathogenetic determinants are a current focus of attention. Although the development of this cancer is influenced by both environmental and genetic factors which are as yet illdefined, genetic studies have revealed gene abnormalities which may be specifically associated with the risk of prostate cancer: changes in genes for the androgen receptor, RNAseL, ELAC2, MSR1, BRCA 1 and 2, HPCX, KLF6, HPC20 and fusion genes, e.g. TMPRSS2-ERG). Despite differing research results from molecular biological studies, these techniques can assist in earlier diagnosis enabling timely initiation of treatment.Methods: Methods and literature: MEDLINE search was performed to collect both original and review articles addressing prostate cancer and genetic risk factors using key words genetics, prostate cancer and risk.Conclusions: A number of potential genetic risk factors/markers has been identified which may in near future contribute to earlier diagnosis of prostate cancer so that earlier treatment can be started. Despite many promising data we have found differing results and therefore we suppose further research should be conducted to achieve more precise conclusion. This review focuses on current knowledge of the genetic factors affecting the development of prostate cancer.
Keywords: Genetics/Prostate cancer/Risk